Brand Image and Social Media in Determining Patient Decisions: The Role of Trust Intervention - Lusiana Agustin; Endang Ruswanti; CSP Wekadigunawan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
This research is based on a decrease in the number of new and old patients in outpatient installation services in 2022. The purpose of this study was to empirically reveal the effect of brand image, social media promotion on patients' decisions to seek treatment, with trust as an intervening variable. This research is included in the quantitative research with a cross sectional study approach, the population used is patients who use health services in outpatient installations, the sample technique uses probability sampling, the sample calculation is by calculating the number of indicators X 5, so that the sample size is 225 respondents with accidental sampling technique. The analytical method used is the three box analysis method and SEM with the help of the Amos program. The results of the analysis conclude that brand image has no effect on decisions, social media promotion and trust have an effect on patient decisions. Brand image and social media promotion affect patient trust and with patient trust, brand image and social media promotion are higher in influencing patient decisions to seek treatment.